Patents and the First Amendment - Dan L. Burk (Washington University Law Review, 2018)
Patents are intended as a means of promoting innovation through private pecuniary incentives. But the patent system has for some time been on a collision course with guarantees of expressive freedom. Surprisingly, no one has ever subjected patent doctrine to a close First Amendment analysis. In this paper I show, first, that patents clearly affect expressive freedom; second, that patents are subject to legal scrutiny for their effect on expressive rights; and third, that patents are not excused from scrutiny by virtue of constituting property rights or by virtue of private discretion. After examining the patent system in terms of familiar First Amendment metrics such as strict scrutiny, narrow tailoring, governmental interest, and least restrictive means, I conclude that even though many patents may survive First Amendment analysis, many will not. Patents, which function as government-sanctioned monopolies, invade core First Amendment rights when they are allowed to obstruct the essential channels of scientific, economic, and political discourse.
Keywords: patent law; intellectual property law; constitutional law; first amendment; expressive freedom; expressive rights; private discretion; strict scrutiny; narrow tailoring; governmental interest; least restrictive means; Intellectual Ventures I v. Symantec 838 F.3d 1307 (Fed. Cir. 2016); Mayer; software patents; patentable subject matter; Patent Exception; State Action; Overbreadth; Vagueness